Türkiye ekonomisinde Kasım 2000-Şubat 2001 iktisadi krizi sonrasında ekonomik aktörlerin yapısı - Erli, İsmail (My University, 2004)
Çalışmada Türkiye ekonomisinin son yirmi beş yıllık süreci dünya ekonomisiyle birlikte tarihsel olarak ele alınmıştır. 1990 sonrası gelişmekte olan ülkelerde meydana gelen krizlerin nedenleri incelenmiş, Türkiye'nin yaşadığı Kasım 2000-Şubat 2001 ekonomik kriziyle ortak yönleri tespit edilmiştir. Kasım 2000-Şubat 2001'de meydana gelen ekonomik krizin toplumda yarattığı değişimi anlamak için ekonomik aktörler; sermaye, emek ve devlet olarak ayrı ayrı ele alınmıştır. Sermaye, kendi içerisinde büyük ve küçük sermaye olarak ayrı ayrı incelenmiştir. Krizin, sermaye içindeki kesimleri nasıl etkilediğini anlamak için imalat sanayi, bankacılık ve tarım sektörleri bir çok boyutu ile incelenmiştir. Emek kesiminin krizden nasıl etkilendiğini anlamak için 1980'den krize kadar ki süreç ele alınmıştır. Ayrıca işsizlik, reel ücretler, gelir dağılımı, sendikaların durumu ve bu alana ilişkin hukuksal değişim de incelenmiştir. Devlet, makroekonomik göstergeler ışığında ele alınmış, kriz sürecinde ve sonrasında yeniden, nasıl yapılandırıldığı araştırılmıştır. Name and Surname:İsmail Erli Research Subdivison:Economics Programme:Development Economics and Economic Fostering Dissertation Ass. Prof. Mehmet Şişman Dissertation Type and Date:Masters Degree- 2004 December Key Words: Crisis, Turkey, Economics, Actors, Capital, Labor, State

Turkish Economics' progress in last 25 years is researched in the study with accordance to the world economic system based on a historical method. The Crisis which took place in developing nations after 1990 is researched and compared with the November 2000- february 2001 economic crisis which happened in Turkey. Economic actors, particularly capital, labor and state are dealt distinctly in order to understand the social change caused by the November 2000-January 2001 economic crisis. In the research, capital is studied seperatly as large capital and petty capital. To explain how different sectors of capital is influenced by the crisis, productive capital, money capital and agriculture sector are studied in their many aspects. In order to understand how working class is affected by the crisis, the period since 1980 is examined in details. To understand how working class as an economic actor is affected from the facts such as unemployment, income distribution, circumstances that trade unions confronted and legal changes concerning the working class are studied.The state is evaluated in accordance with the macroeconomic indicators. Finally restructuring of the state during and after the crisis is studied.
Keywords: Ekonomi, Türkiye; Ekonomik Kriz